HLA Genotyping in Patients with Multiple Sclerosis and Insulin-Dependent Diabetic Patients: Descriptive Study in A Multiplex Libyan Families - Tabagh, Refaat; Darmun, Enas (AlQalam Journal of Medical and Applied Sciences, 2025)
Multiple Sclerosis (MS) is an autoimmune, chronic inflammatory demyelinating central nervous system (CNS) insult initially, and a neurodegenerative disorder eventually. This paper is a descriptive cross-sectional study that involved two Libyan families, with a total number of 8 and 13 members, across two and three generations, respectively. The first family included 2 MS-affected members, and there were 4 MS patients among the second family members. As well as, 3 out of those 6 MS-affected individuals are Insulin-Dependent Diabetic Patients (IDDM). Every MS patient of both families was genotyped for HLA. The HLA-DRB1, DRQB1, and DQA1 were explored. HLA haplotypes were observed in each MS patient, taking into consideration the IDDM comorbidity status. The 3 individuals with MS and type I DM are carriers of the HLA-DRB1*0402-DQB1*0302 pattern. While the patients affected with MS only are carriers of the pattern: HLA- HLA-DRB1*1501-DQB1*0302. In conclusion, this paper brings to our attention that the common HLA genotypes among Libyan MS patients with or without IDDM comorbidity might be the same HLA genotypes among the European MS patients. التصلب المتعدد هو إصابة مناعية ذاتية مزمنة التهابية مزيلة للميالين للجهاز العصبي المركزي في البداية، واضطراب تنكسي عصبي في النهاية. هذه الورقة هي دراسة وصفية مقطعية شملت عائلتين ليبيتين، بإجمالي عدد أفراد يبلغ 8 و13 فردًا، على مدى جيلين وثلاثة أجيال، على التوالي. ضمت العائلة الأولى فردين مصابين بالتصلب المتعدد، وكان هناك 4 مرضى بالتصلب المتعدد بين أفراد العائلة الثانية. بالإضافة إلى ذلك، فإن 3 من هؤلاء الأفراد الستة المصابين بالتصلب المتعدد هم مرضى السكري المعتمدون على الأنسولين. تم تحديد النمط الجيني لكل مريض بالتصلب المتعدد من كلتا العائلتين من أجل مستضدات الكريات البيضاء البشرية (HLA). تم استكشاف HLA-DRB1 وDRQB1 وDQA1. لوحظت أنماط HLA في كل مريض بالتصلب المتعدد، مع الأخذ في الاعتبار حالة الأمراض المصاحبة لمرض السكري المعتمد على الأنسولين. الأفراد الثلاثة المصابون بالتصلب المتعدد ومرض السكري من النوع الأول هم حاملون للنمط HLA-DRB1*0402-DQB1*0302. في حين أن مرضى التصلب المتعدد فقط يحملون النمط HLA- DRB1*1501-DQB1*0302. ختامًا، تلفت هذه الورقة انتباهنا إلى أن الأنماط الجينية الشائعة لـ HLA بين مرضى التصلب المتعدد الليبيين، سواءً كانوا مصابين بمرض السكري المزمن أو غير مصابين به، قد تكون هي نفسها بين مرضى التصلب المتعدد الأوروبيين